WAWASAN MAHASISWA SARJANA KEBIDANAN NON REGULER UNISM MENGENAI PENGGUNAAN DAUN KELOR (MORINGA OLIEFERA) UNTUK MENGATASI ANEMIA DALAM KEHAMILAN - Harisanti, Nova; Susanti Suhartati; Nurul Hidayah (Midwifery And Complementary Care, 2022)
Background : Non-regular undergraduate midwifery students have received courses on midwifery care using a complementary approach, one of which includes the use of herbal remedies. However, these courses have not specifically addressed all types of herbs and their benefits as part of complementary therapy. Objective : To determine the knowledge of non-regular undergraduate midwifery students at UNISM regarding the use of Moringa leaves (Moringa Oleifera) to overcome anemia during pregnancy. Method : This study is descriptive in nature. The population consisted of non-regular undergraduate midwifery students at UNISM. The sampling technique used was systematic sampling. Data collection was conducted using a questionnaire distributed via Google Form. Results : Out of 69 respondents, 35 (50.7%) had good knowledge, 31 (44.9%) had moderate knowledge, and 3 (4.3%) had poor knowledge. Conclusion : The study results show that among non-regular undergraduate midwifery students, 50.7% had good knowledge about the use of Moringa leaves (Moringa Oleifera) to overcome anemia during pregnancy, while 4.3% had poor knowledge. Based on these findings, the researcher assumes that one strategy the Midwifery Study Program could implement is to review the course syllabus (RPS) to ensure that the complementary subject includes specific content on herbal remedies, particularly Moringa leaves. Keywords: Moringa leaves, Knowledge, Anemia